Relative contribution of souvenirs on memorability of a trip experience and revisit intentions: a study of visitors to Rovaniemi, Finland - Sthapit, Erose; Björk, Peter (Scandinavian Journal of Hospitality and Tourism, 2021)
For some tourists, shopping is a “must-do” activity, and many tourists’ purchases can be classified as souvenirs. This study employs a grounded theory approach to explore the central elements of souvenirs that help tourists reminisce about their holiday experiences and encourage their intentions to revisit a place. Based on semi-structured interviews with visitors to Rovaniemi, Finland, from 14 different nationalities, uniqueness, usability and functionality emerged as central elements that prolonged memorability of the travel experience and encouraged revisit intention. This research contradicts studies indicating that a lack of authenticity is an attraction when buying souvenirs and that tourists purchase “genuine counterfeit products” while on holiday due to their lower prices. The managerial implications of this study are that tourism service providers who sell souvenirs in similar contexts should invest more resources on offering objects that represent uniqueness and on local food products and clothes, as well as kitchenware, which represent usability and functionality. Peer reviewed